2008
DOI: 10.1086/528368
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray and Near‐IR Variability of the Anomalous X‐Ray Pulsar 1E 1048.1−5937: From Quiescence Back to Activity

Abstract: We report on new and archival X-ray and near-IR observations of the anomalous X-ray pulsar 1E 1048.1À5937 performed between 2001 and 2007 with the Rossi X-Ray Telescope Explorer (RXTE ), the Chandra X-Ray Observatory, the Swift Gamma-Ray Burst Explorer, the Hubble Space Telescope (HST ), and the Very Large Telescope. Monitoring with RXTE revealed that following its $2001Y2004 active period, 1E 1048.1À5937 entered a phase of timing stability; at the same time, simultaneous observations with Chandra and HST in 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 68 publications
11
82
2
Order By: Relevance
“…The variations in the spin-down torque of SGRs and AXPs are remarkable in their amplitude and longevity; the spin-down rate is observed to increase smoothly over a period of months, by up to a factor $8 (Kaspi et al 2001;Woods et al 2002Woods et al , 2007Tam et al 2008;Camilo et al 2007bCamilo et al , 2008. The strength of the torque variations correlates roughly with the level of activity that the magnetar has sustained over the preceding years, but this correlation is only indirect.…”
Section: Variability In the Open-field Voltage Due To Magnetospheric mentioning
confidence: 97%
“…The variations in the spin-down torque of SGRs and AXPs are remarkable in their amplitude and longevity; the spin-down rate is observed to increase smoothly over a period of months, by up to a factor $8 (Kaspi et al 2001;Woods et al 2002Woods et al , 2007Tam et al 2008;Camilo et al 2007bCamilo et al , 2008. The strength of the torque variations correlates roughly with the level of activity that the magnetar has sustained over the preceding years, but this correlation is only indirect.…”
Section: Variability In the Open-field Voltage Due To Magnetospheric mentioning
confidence: 97%
“…In 2007 March, 1E 1048.1−5937 showed a pulsed flux increase, which was followed by a spin-up glitch (Dib et al 2009). Subsequent observations with imaging X-ray telescopes revealed that the total flux increased by a factor of ≈7, while the pulsed fraction decreased significantly from ≈70% to ≈30% (Tam et al 2008). The observed anti-correlation between the total flux and the pulsed fraction was attributed to a growing hot spot on the neutron star surface (Tam et al 2008;seeÖzel & Güver 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Tam et al (2008) reported a 2-10 keV rms pulsed fraction of ≈70% for 1E 1048.1−5937, using several Chandra observations throughout 2006 when the source showed no activity. In 2007 March, 1E 1048.1−5937 showed a pulsed flux increase, which was followed by a spin-up glitch (Dib et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations